Synthesis and Characterization of Novel Schiff Bases Containing Isoxazoline or Pyrazoline Unit - Khazaal, M. S.; Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work involves synthesis of novel Schiff bases derivatives contining isoxazoline or pyrazoline units starting with chalcons . 4-Aminoacetophenone was react with pnitrobenzaldehyde or p-chlorobenzaldehyde in basic medium giving chalcones [I]a,b by claisenschemidt reactions. The chalcones [I]a,b were reacted with hydroxylamine hydrochloride giving isoxazolines [II]a,b  in basic medium. The chalcone [I]a could also reacted with hydrazine hydrate to give pyrazolines [III]a  . The novel Schiff bases with structural formula [VIII]n , [IX]n , [X]m and [XI]m were prepared by the reaction of amino compounds ; isoxazoline [II]a,b and pyrazolines [III]a with monoaldehydes [VI]n and dialdehydes [VII]m , respectively in dry benzene using drops of glacial acetic acid as a catalyst with reflux . All the synthesized compounds have been characterized by melting points , FTIR , UV-Vis and 1HMNR (of some of theme) spectroscopy